Spleen and Liver Stiffness Evaluation by ARFI Imaging: A Reliable Tool for a Short-Term Monitoring of Portal Hypertension? - Andreas Binzberger; Mark Hänle; Matthias Pfahler; Wolfgang Kratzer; Thomas Seufferlein; Eugen Zizer (International Journal of Hepatology)
Background. Assessment of hepatic venous pressure gradient (HVPG) is the most reliable, though invasive method for evaluation of portal hypertension. Non-invasive, elastography-based techniques are well established in diagnosis, but not in monitoring of portal hypertension. The aim of our prospective study was to determine the value of acoustic radiation force impulse (ARFI) elastography technique of the liver and spleen in diagnosis and monitoring of portal hypertension. Methods. We prospectively assessed portal hypertension by HVPG and corresponding elastography of the liver and spleen in 31 patients with liver cirrhosis and an indication for primary prophylaxis by non-cardio selective beta-blockers. Investigations were performed at baseline and a follow-up visit after 6-8 weeks. To address the known large variability of values for spleen elastography, well-defined corresponding areas in the spleen were used for baseline and follow-up elastography. Sensitivity, specificity, and AUC-ROC values for both spleen and liver elastography monitoring of portal hypertension were calculated. Results. Liver but not spleen elastography significantly correlated with HVPG results and was suitable for initial evaluation of portal hypertension. However, changes in HVPG results did not show any correlation with alterations of ARFI values from baseline to follow-up visits both for liver and spleen elastography. Spleen stiffness results were not homogeneous across the whole organ differing significantly between the upper, hilar, and bottom placed investigation areas. Conclusions. In this prospective study ARFI-based assessment of liver elastography showed itself suitable for initial assessment but not for monitoring of portal hypertension. Spleen elastography was not appropriate for both, evaluation and monitoring of portal hypertension. A possible explanation for this new data that are in some contrast to previously published results is the degree of portal hypertension in our study, a comparatively short follow-up period, and well-defined investigation areas for spleen elastography in repetitive ARFI investigations. This trial is registered with NCT03315767.